Concept theory in library and information science: an epistemological analysis - Machado, Luís Miguel Oliveira; Martínez-Ávila, Daniel [UNESP]; Simões, Maria da Graça de Melo (Emerald, 2019)
Purpose: The purpose of this paper is to discuss the literature on concept theory in library and information science (LIS) from an epistemological perspective, ascribing each paper to an epistemological family and discussing their relevance in the context of the knowledge organization (KO) domain. Design/methodology/approach: This paper adopts a hermeneutic approach for the analysis of the texts that compose the corpus of study following contingency and categorical analyses. More specifically, the paper works with Bardin’s contingency analysis and follows Hjørland’s families of epistemologies for the categorization. Findings: The analysis corroborates the observations made for the last ten years about the scarcity of studies on concept theory in LIS and KO. However, the study also reveals an epistemological turn on concept theory since 2009 that could be considered a departure from the rationalist views that dominated the field and a continuation of a broader paradigm shift in LIS and KO. All analyzed papers except two follow pragmatist or historicist approaches. Originality/value: This paper follows-up and systematizes the contributions to the LIS and KO fields on concept theory mainly during the last decade. The epistemological analysis reveals the dominant views in this paradigm shift and the main authors and trends that are present in the LIS literature on concept theory.
Keywords: Knowledge organization; Knowledge organizations